Exploring spatial differentiation and obstacle factors of rural multifunctionality in metropolitan suburbs of China: Applying the “need- function-factors” integrated framework - Linnan Tang; Wei Zhou; Yu Liu; Yanmin Ren (Ecological Indicators, 2025)
Rural multifunctionality (RMF) is gaining attention in metropolitan suburbs for addressing the diverse needs of both urban and rural residents, yet spatial differentiation studies from a needs-based perspective remain limited. The study develops a “need-function-factors” framework to analyze RMF in China’s metropolitan suburbs, focusing on rural production, living, and ecological functions. Using the Beijing Ecological Conservation Area (BECA) as a case study, it establishes an evaluation index system with 27 indicators across eight categorized needs. By applying simple linear weighting, spatial mismatch index, and an obstacle diagnosis model, the study explores the spatial differentiation characteristics and identifies key obstacles at the township scale. The main results show that: 1) Townships in BECA are predominantly characterized by ecological functions, with plain areas excelling in production and living functions, while mountainous areas are stronger in ecological functions. The spatial patterns of rural production, living, and ecological functions are driven sequentially by specialty products need, living convenience need, and ecological conservation and regulation need respectively. 2) Main obstacles to rural production, living, and ecological functions relate to the safety and efficiency need, living convenience need, and ecological conservation and regulation need, highlighting the necessity to prioritize baseline needs. The varying impacts of obstacles across regions underscore the complexity of functional development. This study provides valuable insights for sustainable regional development, offering guidance for future land consolidation, ecological restoration, and enhancement of ecosystem services in China’s metropolitan suburbs.